Development of honey/chitosan nanofibrous scaffolds loaded with natural materials and bacteriophage: Evaluation of their antimicrobial and wound healing activities. - Sarhan, Wesam Awad (AUC Knowledge Fountain, 2016)
Non-healing wounds represent a serious health care burden with major socioeconomic impacts. Bacterial infection of the wound site further complicates the healing process as it stimulates the immune system which in turn prolongs tissue inflammation thus further delaying the healing process. Moreover, wound associated bacterial contamination usually develops resistance to commonly used antibacterials leading to increased risk of systemic infections. Treatment of infected wounds is being achieved via different kinds of dressings in association with antibacterials, antiseptics and wound healing materials. Currently, however there has been a noticeable shift towards advanced antimicrobial wound care as a possible solution for the problem. Advanced antimicrobial wound care are dressings that can be loaded with either antibiotics or antiseptics and are able to reduce or eliminate the bacterial load at the wound site. However, one of the major challenges associated with such dressings is the continuous emergence of antibiotic resistant strains as well as the observed damage of healthy tissues in case of antiseptics. Moreover, it has been argued that the antimicrobial efficacy alone of an advanced dressing is insufficient and other properties that enhance the wound healing process are also required. To help provide a solution for this challenge, this study aims to investigate the development of a novel series of advanced antimicrobial wound dressings that are based on honey and chitosan and fabricated in the nanofibrous form. Honey and chitosan are well known for their wound healing and antibacterial properties. Moreover, developing the dressings in the nanofibrous structure allows enhancement of the wound healing process. Electrospinning technique was adopted to fabricate novel nanofibrous wound dressings based on high honey and chitosan concentrations (HPCS). Natural extracts namely: Cleome droserifolia (CE) and Allium sativum (AE) and apitherapeutics namely: bee venom (BV) and propolis (Pr) as well as bacteriophages (PS1) were loaded within the fabricated honey chitosan based nanofibrous dressings to enhance their antibacterial activity and extend it against resistant bacterial strains as well as increase their wound healing abilities. The fabricated series of nanofibrous dressings, HPCS, HPCS-AE, HPCS-CE, HPCS-AE/CE, HPCS-BV, HPCS-Pr and HPCS-BV/PS1 demonstrated enhanced wound healing abilities and variable antibacterial effects against the examined bacterial strains as compared to the commercial wound dressing Aquacel Ag. Most importantly, the developed series of nanofibrous dressings demonstrated enhanced biocompatibility as compared to the Aquacel Ag that demonstrated noticeable cytotoxicity. Thus, the developed series of nanofibrous wound dressings that are based on natural materials represent competitive candidates to be used as effective wound dressings.